Soft skills in social and humanities education of the digital age: philosophical and educational dimension - Krasilnikova, Olena (Skhid, 2026)
The article offers a philosophical and educational analysis of the phenomenon of soft skills within the context of socio-humanitarian education in the digital age. The relevance of the study is determined by the profound transformations of the contemporary educational space driven by digitalization, globalization processes, and changes in the nature of social and professional interaction. The paper substantiates the thesis that soft skills cannot be reduced to a set of applied or purely instrumental competencies oriented exclusively toward labor market demands. Instead, they are conceptualized as a multidimensional socio-cultural phenomenon associated with the formation of humanitarian rationality, value-based reflection, ethical responsibility, and the capacity for reflective communication. The study demonstrates that under conditions of the digital transformation of education, there is a growing need to reconsider the role of socio-humanitarian knowledge as a space for the development of critical thinking, communicative competence, emotional intelligence, empathy, and moral sensitivity. Socio-humanitarian disciplines are viewed as a key resource for shaping responsible agency among higher education students, enabling reflexive interaction in contexts of digital communication, information overload, and increasing ethical challenges. The methodological framework of the research is grounded in philosophical and educational analysis, interdisciplinary and axiological approaches, as well as empirical research methods aimed at identifying the potential of socio-humanitarian disciplines in fostering soft skills among higher education students. Based on theoretical reflection and empirical findings, the article substantiates the significance of socio-humanitarian education as a determining factor in the development of social maturity, professional adaptability, and the capacity for responsible participation in public life within a digital society. The study concludes by emphasizing the necessity of integrating a philosophical and value-oriented dimension into contemporary higher education practices of soft skills development.